Fabrication of a flexible inner prosthetic socket via the FGM technique - Al-Araji I.Z.H.; Satgunam M.A.P.; Abd Manap A.N.B.; Resan K.K.; Muhammad A.K. (Emerald Publishing, 2025)
Purpose: The purpose of this study was to fabricate a flexible inner socket with enhanced stiffness and hardness distribution by using the functional gradient method (FGM). The FGM technique can improve the comfort and flexibility of amputees through the use of a socket that is built via the direct method. Design/methodology/approach: Six flexible inner socket samples were fabricated with varying weight fractions of rice husk ash-to-silicone rubber. The tensile strength and hardness of each sample were assessed. Then, numerical analyses were conducted using SOLIDWORKS software to evaluate the pressure distribution on the inner and outer layers of the flexible socket. Findings: The hardness and stiffness of the fabricated flexible inner socket gradually increased with the weight ratio of rice husk ash-to-silicone rubber, so when it was in contact with the skin, it approximated the stiffness and hardness of the skin to ensure comfort, and when reaching a higher value in the socket contact layer, it prevented penetration through the flexible inner socket. In addition, the pressure distribution at the external layer of the flexible inner socket has improved. Research limitations/implications: A budget of US$500 limited the research to create a flexible inner socket that keeps the socket from penetrating the skin. Practical implications: The FGM technique created a flexible inner socket that balances hardness and stiffness to ensure comfort and prevent wounds for its users, lower limb amputees. The commercial value resides in the accessibility of a secure and comfortable flexible inner socket for amputees worldwide, enabling them to overcome the issue of excessive stiffness typically associated with sockets made using the direct method. Originality/value: This study introduces the use of FGM to fabricate a flexible inner prosthetic socket with enhanced stiffness and hardness distribution. The approach of using varying weight fractions of rice husk ash-to-silicone rubber to improve the comfort and flexibility of prosthetic sockets is a novel contribution to the field. Given the high stiffness of flexible internal sockets and their ability to maintain flexibility in the part in contact with the skin, such sockets manufactured using this method prevent pain and skin ulcers that previously occurred when sockets are manufactured via the direct method. ? 2024, Emerald Publishing Limited.